Genetic Heterogeneity and Risk of Acute Respiratory Distress Syndrome - Meyer, Nuala J.; Christie, Jason D. (Seminars in Respiratory and Critical Care Medicine, 2013)
Genetic variation explains some of the observed heterogeneity in patients' risk for developing the acute respiratory distress syndrome (ARDS). Although the lack of extant family pedigrees for ARDS precludes an estimate of heritability of the syndrome, ARDS may function as a pattern of response to injury or infection, traits that exhibit strong heritability. A total of 34 genes have now been reported to influence ARDS susceptibility, the majority of which arose as candidate genes based on the current pathophysiological understanding of ARDS, with particular focus on inflammation and endothelial or epithelial injury. In addition, novel candidate genes have emerged from agnostic genetic approaches, including genome-wide association studies, orthologous gene expression profiling across animal models of lung injury, and human peripheral blood gene expression data. The genetic risk for ARDS seems to vary both by ancestry and by the subtype of ARDS, suggesting that both factors may be valid considerations in clinical trial design.
Keywords: genetic association study; genetic variation; polymorphism; ARDS; ALI